Analysis of the effectiveness of regulation on financial health of Spanish local governments. Issue 3 (3rd July 2022) - Pina, Vicente; Bachiller, Patricia; Ripoll, Lara
ABSTRACT: The need to reduce public sector costs and debt has resulted in the implementation of requirements in many countries. Spain belongs to a group of countries which monitor the financial health of their local governments, using financial indicators enforced by law, and reporting this information periodically. The objective of this paper is to analyse whether the introduction of the 2012 Spanish legislation regarding fiscal stability and budgetary balance and Ministry of Finance Order 1781/2013, which develop new indicators, have led to improvements in the financial health of local governments. The results of our analysis show that the introduction of legal requirements is effective and that the disclosure of indicators for benchmarking purposes has been beneficial and positive, although this is not so in all cases. The practical implication of this study is that the dual demands of evaluating the financial situations of local governments and disclosing this information reinforce their responsibility with respect to the general interest. This enables the comparative evolution of indicators, concluding that requirements are also needed to ensure that the goals are achieved, thereby helping to restore the reliability and transparency of their activities.